Pengaruh Citra Merek dan Kesadaran Merek Terhadap Keputusan Pembelian Air Minum dalam Kemasan (AMDK) Merek AQUA (Studi Kasus Konsumen di Kawasan Makam Gus Dur Tebuireng Jombang) - Muhammad Izzuddin Amin (BIMA : Journal of Business and Innovation Management, 2019)
This research use analysis technique quantitative data with data collecting observation use primer data that is get from population. A sample in this research was 125 respondents. The sample took by nonprobability sampling Technique actually purposive sampling which is technique take from the element of population and chosen from respondent’s voluntary who represent of the population and chosen to be a sample. Technique of data analysis use Regresi Linier Berganda. The result shows that: (1) Image label has positive influential and significant of purchasing decision. (2) Realizing label has positive influential and significant of purchasing decision. (3) Both of image label and realizing do simultaneously of purchasing decision mineral water which is has label “AQUA” (Study case Consumer at Kawasan Makam Gus Dur in Tebuireng Jombang)